Al-Ashmawi dan Nalar Kritis Shariat: Menemukan Kembali Dimensi yang Hilang dari Wacana Shariat Islam - Yusuf Hanafi (Islamica: Jurnal Studi Keislaman, 2008)
Shariah is the heart of Islam because it handles the most fundamental aspects of the religion. Ironically however, Shari?ah is the most misunderstood dimension of Islam. What we currently believe as Shari?ah may not be Shari?ah. And the reverse may be true that what we consider as non-Shari'ah, may in fact be Shari'ah. It is here that reconstructing our understanding concerning the true meaning of Shari?ah becomes a matter of necessity. Having this in mind, we are interested in elaborating the critical views of al-Ashmawi on the notion of Shari?ah hoping that this will help us to discover the missing and yet the true- dimension of Shari'ah. Al-Ashmawi on the whole, is critical against the jargon that only associates the Shari?ah with its formalization and application.